2011
DOI: 10.1186/1471-244x-11-162
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive flexibility in verbal and nonverbal domains and decision making in anorexia nervosa patients: a pilot study

Abstract: BackgroundThis paper aimed to investigate cognitive rigidity and decision making impairments in patients diagnosed with Anorexia Nervosa Restrictive type (AN-R), assessing also verbal components.MethodsThirty patients with AN-R were compared with thirty age-matched healthy controls (HC). All participants completed a comprehensive neuropsychological battery comprised of the Trail Making Test, Wisconsin Card Sorting Test, Hayling Sentence Completion Task, and the Iowa Gambling Task. The Beck Depression Inventory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
86
2
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 50 publications
7
86
2
7
Order By: Relevance
“…Studies have shown that individuals with eating disorders have deficits in neuropsychological functioning [1,2,3,4,5,6,7,8]. These deficits may decrease both treatment motivation and the efficacy of psychological interventions and may even perpetuate the illness [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that individuals with eating disorders have deficits in neuropsychological functioning [1,2,3,4,5,6,7,8]. These deficits may decrease both treatment motivation and the efficacy of psychological interventions and may even perpetuate the illness [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Set-shifting concerns the ability to move back and forth between multiple tasks, operations or mental sets; it represents cognitive flexibility. Difficulties in set-shifting have been found in women with current and past AN and BN [7] in a variety of neuropsychological tests [2,3,4,5,6,8]. Weak central coherence refers to superior detail processing and weak global integration, which is present in individuals with current AN and BN [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Además, a estos pacientes se les dificultan aquellas actividades que exigen realizar simultáneamente varias tareas, lo que reduce su capacidad para involucrarse en experiencias nuevas o usar el tiempo en forma más productiva. Inflexibilidad que afecta no solo su desempeño interpersonal y cognitivo (Abbate-Daga et al, 2011;Lezak, 2012), sino también su respuesta al tratamiento (Crane, Roberts y Treasure, 2007), constituyendo un factor agravante del trastorno .…”
Section: Introductionunclassified
“…Estos estilos de pensamiento, que con frecuencia coinciden con rasgos de personalidad relacionados con el trastorno obsesivo-compulsivo , están presentes no sólo en fases agudas, sino aún después de haber mejorado sus condiciones clínicas (Abbate-Daga et al, 2011;Aloi et al, 2015;Darcy, Fitzpatrick y Lock, 2016;Roberts et al, 2010;Stedal, Frampton, Landro y Lask, 2012). llamada "Con la cabeza en las nubes" (CCN).…”
Section: Introductionunclassified
“…Depressive disorders and other psychiatric disorders in parents can influence adaptation issues or the adolescents' psychopathology [31]. The specific lack in parenting skills is linked to disorders of somatization [32], eating disorders [33][34][35][36] and borderline personality [37,38]. On the other hand it has been ascertained that conflicts and intra-family stress predispose to disorders such as substance abuse in adolescents [39].…”
Section: Commentarymentioning
confidence: 99%